Effect of linkage design of an elbow implant on micro-motion: a finite element analysis - Heidari, Milad; Rahmanivahid, Pooyan (International Journal of Engineering and Technology, 2020)
The major reason for total elbow arthroplasty failure is loosening. Loosening is the outcome of a detrimental mechanical incident, which causes the failure of the bond between the bone bed and implant. The shape of the linkage of an elbow implant has a considerable role to transfer a portion of the load to the cement-bone and cement-implant interfaces. Therefore, in this study, the linkage of an elbow implant was modified to reduce loosening using finite element analyses. Elbow bone was constructed using image processing software. Linkage components were modeled using modeling computer-aided design software. Material properties and boundary conditions were applied. The stress distribution and micro-motion were obtained in linkage component and cement-implant-bone interfaces respectively. Based on our results, sub-design 3B proved less interface micro-motion compared to others. Our study showed that modification of a linkage reduces the micro-motion transferred to bone-cement and cement-implant interfaces. A reduction of micro-motion, through linkage modification, may improve the clinical outcomes.Â Â